2019
DOI: 10.1111/jbi.13738
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐mediated filtering drives contrasting patterns of species richness and functional diversity across montane bird assemblages

Abstract: Aim: Most studies of diversity changes along elevational gradients show a synchronous change in taxonomic, functional and phylogenetic diversity, such that all decline with elevation or show a mid-elevation peak. However, some studies show asynchronous changes, which challenge us to explain their assembly. Here we used functional trait variation and niche spacing to test the roles of environmental filtering and competition-driven niche separation in assembly and biodiversity patterns across an elevational grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 53 publications
1
38
0
1
Order By: Relevance
“…In functional diversity studies, dietary guild and vertical stratum have commonly been related to resource requirements and species' sensitivity to habitat change (Petchey et al 2007). Wing chord and body mass have been used to calculate dispersal ability (Zhang et al 2020). Breeding phenology and fecundity responses to environmental stress conditions include a combination of fecundity-survival schedules and behavioral strategies that yield the highest fitness at higher elevations (Badyaev and Ghalambor 2001).…”
Section: Data Acquisition and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In functional diversity studies, dietary guild and vertical stratum have commonly been related to resource requirements and species' sensitivity to habitat change (Petchey et al 2007). Wing chord and body mass have been used to calculate dispersal ability (Zhang et al 2020). Breeding phenology and fecundity responses to environmental stress conditions include a combination of fecundity-survival schedules and behavioral strategies that yield the highest fitness at higher elevations (Badyaev and Ghalambor 2001).…”
Section: Data Acquisition and Preparationmentioning
confidence: 99%
“…Breeding phenology and fecundity responses to environmental stress conditions include a combination of fecundity-survival schedules and behavioral strategies that yield the highest fitness at higher elevations (Badyaev and Ghalambor 2001). In our study, trait data for most species were collected from individuals captured by mist-netting at the study site (Zhang et al 2020), with missing values for species measured on museum specimens from localities as close as possible to the study site, and from published literature about the birds of southern China (Zhao 2001; Appendix S1: Table S3).…”
Section: Data Acquisition and Preparationmentioning
confidence: 99%
“…In Yunnan, Yang et al [47] found 43 species, and surveys in Anhui Province report 14-31 species [22,48]. An extensive survey in a protected forest area at similar geographical latitude in the Nanling Mountains, Guanzhou Province, reported 80 species [18], and a year-long survey found 51 species in Dinghushan Nature Reserve, in the neighbouring Guangdong Province [49]. Unfortunately, a more quantitative comparison is not possible, because most of the pre-existing literature contains occurrence lists and descriptive notes only.…”
Section: Discussionmentioning
confidence: 99%
“…China, with its 1300+ species, is a country with a high diversity of birds, especially in the south [16]. Previous studies of forest birds in the south of China detected >110 species in traditionally managed forests [17] or 80 species in protected ones [18]. Agroforestry [19] and shade-grown coffee [20] or cocoa [21] can support several forest-based bird species in Asia, and Central-South America.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize, though, that the magnitude and direction of the effects of trait resolution on perceived community structure are currently poorly known, and this bias may not be limited to the narrow conditions presented here. Moreover, our conceptual predictions assume a single strong process, but non‐random structure is more difficult to detect when multiple interacting processes are acting upon a community (Aiba et al., 2013; Götzenberger et al., 2016; Kraft & Ackerly, 2010), a more realistic expectation (Spasojevic & Suding, 2012; Zhang et al., 2020). It is thus likely that, in real communities, inflated convergence resulting from low trait resolution may lead to incorrectly concluding environmental filtering to be a driving factor when the true pattern is random (Type I error).…”
Section: The Predicted Effects Of Trait Resolution On Detection Of Asmentioning
confidence: 99%